Perspectives of Faculty Members at Shahid Beheshti School of Dentistry on Teacher Evaluation Process: Opinions Of Faculty Members Dentistry School About the Teacher Evaluation - Jafari , Soudeh; Mehdipour , Masoomeh; Shafieizadegan, Hosein (Journal of Dental School, 2025)
Objectives: Evaluation is an essential and comprehensive process for all organizations. Evaluation has become very common in Iran during the past decade, and different universities assess their teachers through various methods, including various questionnaires. This research aimed to evaluate the perspectives of faculty members about the teacher evaluation process. Methods: This qualitative observational study involved 98 faculty members from Shahid Beheshti School of Dentistry who were willing to participate. Data were collected using a researcher-made questionnaire. The questionnaire items were selected using previous research conducted in this field. After verifying their validity and reliability, 10 items were chosen. Data analysis was conducted using Pearson correlation coefficient and linear regression tests (P<0.05). Results: This study involved 98 university professors, with a mean teaching experience of 12.95±9.01 years. The mean score of their opinions about the evaluation system was 37.30 ± 4.75. The opinion of faculty members regarding the evaluation system had a significant inverse relationship with teaching experience (p<0.001) and male gender (p=0.025). The results showed that 80.7% of the participants believed that the evaluation process effectively improved their teaching, although 66.3% did not approve the current evaluation method. Conclusion: Most faculty members believed that evaluation positively affected the quality of their teaching, although the current teaching methods were not satisfactory.